Analisis Pendidikan Humanis Ki Hadjar Dewantara pada Program “Satu Siswa, Satu Prestasi” - Suci Romadhona; Mohammad Shidqi Fadli; Mohammad Shofiyulloh; Rulam Ahmadi; Ifit Novita Sari (Universitas Nusantara PGRI Kediri, 2023)
Education is one of the most important needs in life. The success of education is seen from the achievements obtained. Achievements are not only in academic form, but also in non-academic form. In the era of globalization, educational institutions are competent in offering their respective superior programs. This is because educational institutions must be able to answer the challenges of the development of the times according to the needs of the community. The One Student, One Achievement program implemented at Al-Rifa'ie Modern Middle School aims to train students' honesty and see students' non-academic achievements. The purpose of this study is to explore in detail the implementation of One Student, One Achievement at Al-Rifa'ie Modern Middle School. This study uses a qualitative approach. Data collection was carried out by conducting observations followed by documentation. Observations were carried out by directly observing the One Student, One Achievement process, while documentation was carried out by looking at student summary documents. The results of the study indicate that the One Student, One Achievement program is effective to be implemented at the junior high school level. With the One Student, One Achievement program, it is hoped that students will be accustomed to having good character.